ANTESEDEN DAN KONSEKUENSI DARI CUSTOMER SATISFACTION PADA RUMAH SAKIT UMUM DAERAH DI SURABAYA - Sri Mulyono Joko Purnomo Purnomo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
The background of this study was to entrust the health services to hospitals on quality, consumers willhave the brand attitude, brand attitude of consumers to the brand overall evaluation. Or a positiveassessment of the brand can lead customers into believing the services provided so that the companybelieves this attitude that led to patient satisfaction and intent to return again using the sameservice.Customer satisfaction is the impact of the quality of the results, the quality of the interaction,the quality between the patient and the patient and medical personnel. When quality reliable whichhas prestige in this regard may lead the consumer to use the services and then the attitude of loyalty isformed. With the level of consumer loyalty can deliver a positive attitude towards the Hospital thatconsumers can trust and become advocates in maintaining quality. The aim of this study was toanalyze the effect of the importance of quality outcomes, Interaction Quality and Peer-to-peer Qualityto create the Customer Satisfaction which would impact on Customer Loyalty. This study design usinghypothesis testing aims to examine the relationship between the variables studied. a sample of 150patients were examined you ever come to hospitals Surabaya. The sample used was purposivesampling. The model used is based on research criteria. Analysis of the data used in this study werecollected by using questionnaires, by providing a written statement to the respondent. In addition, therespondents to respond to the statement given. Questionnaires were administered closed and wherethe answer is already available, In this study before distributing questionnaires to test the validity andreliability of research instrument to get a measuring instrument valid and reliable. Results of this studyconcluded that the Outcome Quality, Interaction Quality, Peer-to-peer Quality positive and significantimpact on Customer Satisfaction. Customer Satisfaction positive and significant impact on customerloyalty. Overall service hospital in Surabaya, especially Hospital Dr Soetomo give pelyanan good, theservice pleasant, decent and positive so that the patient or the consumer will invite friends and familyto seek treatment in hospitals in Surabaya is and respondents did not miss the opportunity to tellothers things -it is good about the hospital in Surabaya. If consumers hear bad news or negative aboutthe hospital in Surabaya, consumers will straighten that is not good news because consumers are sureto invite friends and family to the hospital in Surabaya for treatment.Keywords : Quality outcomes, interaction quality and peer-to-peer quality, customer satisfaction andcustomer loyalty.